Exploratory study on BRAC's NGO cooperation project - Karim, Fazlul; Begum, Shamim Ara; Chowdhury, Kabir; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2020)
BRAC embarked on an NGO Cooperation Project to enhance efficiency of the small and medium NGOs in effective micro-finance management vis-a-vis augmentation of micro-finance activities for poverty alleviation. The newly set up NGO Cooperation Unit (NCU) at BRAC facilitates the implementation of the project. The NCU extended support to 74 NGOs (hereinafter called partner organisations or POs) between 1995 and 1999. Of the 74 POs, 59 were given both training and credit support, while 13 only training. BRAC disbursed maximum Tk. 1,400,000 to each PO as credit in 12 installments. For this BRAC charged 5% service charge from the recipient POs per annum.